Antibiotic prescribing errors generated by the use of an electronic prescribing system in the emergency department: A mixed-method study. - Ahmad Z. Al Meslamani; Derar H. Abdel-Qader; Noura Ziad; Nadia Al Mazrouei; Asma A. El-Shara; Husam El Sharu; Eman Merghani Ali; Rand Haider Al Zahawi; Samah Bahy Mohammed Ebaed; Osama Mohamed Ibrahim (GarVal Editorial Ltda., 2022)
Context: Inappropriate prescribing of antibiotics can result in serious patient harm. Aims: To investigate the incidence, nature, clinical severity, and causes of antibiotic prescribing errors (APEs) in the emergency department (ED) of a large hospital in Jordan. Methods: A mixed-method approach was used to explore the incidence and types of APEs by direct observation of electronic prescriptions (EPS) of antibiotics over four weeks, and to identify causes of errors by semi-structured interviews with ED physicians. The clinical severity of APEs was rated by a committee of experts. SPSS V26 and NVivo 10 were used for the analysis of quantitative and qualitative data, respectively. Results: The incidence of APEs caused by the use of EPS was 4.3%. Wrong quantity (32.62%), wrong dose (15.25%), and duplicate drugs (13.55%) were identified as the most common types of APEs. More than one-third of APEs identified were deemed clinically significant, seven were serious, and one was lethal. Minor and significant antibiotic APEs across physicians who attended workshops on EPS and those who did not were 75.00% versus 46.77% (p = 0.001) and 18.75% versus 52.41% (p = 0.013), respectively. Three major causes of errors were identified: 1) System-related (system crash, drop-down menu), 2) user-related (lack of computer skills), and 3) workplace-related (overcrowding, inadequate staffing). Conclusions: APEs generated by the use of EPS were common in EDs in Jordan, clinically significant, and multifactorial. Further research is required to cover pharmacists' perspectives of this kind of errors.